2018
DOI: 10.3390/en11123410
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Energy Storage Potentials of Waste Biomass: Oil Palm Leaf- and Palm Kernel Shell-Derived Activated Carbons

Abstract: In this study, activated carbons (ACs) were produced from oil palm leaves (OPL) and palm kernel shells (PKS) using different concentrations (0%, 11%, and 33%) of H3PO4 as the activating agent. The Brunauer–Emmett–Teller (BET) results indicated that surface area decreases with the decreasing of the concentration of the H3PO4 in the following order: AC from oil palm leaves was (OPLAC-0% H3PO4) < (OPLAC-11% H3PO4) < (OPLAC-33% H3PO4), with the BET surface area values of 37, 760, and 780 m2/g, respectively. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 72 publications
3
18
0
Order By: Relevance
“…Palm Kernel shell (PKS) is the sustainable source and usually it is burned to dispose causing greenhouse effect and resulting in a negative impact to the environment. A lot of research efforts are being done to recycle and utilize the agricultural waste for the betterment instead of open burning which making a negative impact to the environment and causing ozone layer depletion 15 . Application of agricultural waste as an adsorbent for the removal of pollutants, especially heavy metal ions from water and that is a cost effective and eco-friendly technique for the treatment of heavy metal ions contaminated water.…”
Section: Introductionmentioning
confidence: 99%
“…Palm Kernel shell (PKS) is the sustainable source and usually it is burned to dispose causing greenhouse effect and resulting in a negative impact to the environment. A lot of research efforts are being done to recycle and utilize the agricultural waste for the betterment instead of open burning which making a negative impact to the environment and causing ozone layer depletion 15 . Application of agricultural waste as an adsorbent for the removal of pollutants, especially heavy metal ions from water and that is a cost effective and eco-friendly technique for the treatment of heavy metal ions contaminated water.…”
Section: Introductionmentioning
confidence: 99%
“…Despite a monumental effort made by governments and policy makers around the world to address energy and environmental issues, the global energy crisis still remains humanity's concern, owing to the rapidly growing population and sustainability issues associated with fossil fuel reserves. Thus, the increased demand for environmentally-friendly, good-performance and renewable energy storage devices [1,2]. Storage systems, based on electrochemical reactions such as batteries and supercapacitors for renewable energy technologies, have tremendous advantages due to their high quality in energy storage and delivering on demand and in load levelling of the electrical grid [3].…”
Section: Introductionmentioning
confidence: 99%
“…As a facile and scalable production process, first, graphene oxide was prepared as described by Marcano et al (2010), with a slight modification as previously reported (Nasir et al 2017(Nasir et al , 2018. Briefly, the EFB-derived graphite-like powder (3 g) was mixed with concentrated H2SO4/H3PO4 (360:40 mL), and 18 g of KMnO4 was gradually added to the mixture, raising the temperature of the reaction mixture to 35 to 40 °C.…”
Section: Preparation Of Reduced Graphene Oxide Using Lignocellulosic Materials Derived From Oil Palm By-productmentioning
confidence: 99%